Kompetensi Social Media Specialist di Stasiun Radio Bandung - Alifia Putri Rahmawaty; Nova Yuliati (UNISBA Press, 2024)
Abstract. Social Media Specialist competency has its own urgency in maintaining the sustainability of social media management. Successful social media management not only depends on a consistent online presence, but also depends on the special skills possessed by a Social Media Specialist. This research focuses on the competence of the Social Media Specialist at Radio Oz Bandung, who manages and implements digital communications via social media. This research aims to find out about the communication competence of Social Media Specialist Radio Oz Bandung by using it in social media management using Brian Spitzberg and Willian Cupach's Communication Competency theory. The research method used is quantitative with a descriptive study approach. The results of this research show that to maintain consistency, Social Media Specialist Radio Oz Bandung must have the motivation to always look for the latest trends that are of interest to the public on various social media platforms. Supported by the content and procedural knowledge they have in optimizing social media, the knowledge that Radio Oz Bandung's social media specialists have in managing content is very important to ensure that the content is interesting to the audience. In addition, Social Media Specialist Radio Oz Bandung is developing its content strategy which focuses on lifestyle, music and radio. With that, Radio Oz Bandung's Social Media Specialists in building effective digital communication, they rely on technical skills and communication skills such as copywriting, editing and design to manage content that attracts the audience's attention. Abstrak. Kompetensi Social Media Specialist memiliki urgensi tersendiri dalam menjaga keberlanjutan pengelolaan media sosial. Keberhasilan pengelolaan media sosial tidak hanya tergantung pada kehadiran online yang konsisten, tetapi juga bergantung pada keahlian khusus yang dimiliki oleh seorang Social Media Specialist. Penelitian ini difokuskan pada kompetensi Social Media Specialist di Radio Oz Bandung, yang mengelola dan melaksanakan komunikasi digital melalui media sosial. Penelitian ini bertujuan untuk mengetahui kompetensi komunikasi yang dimiliki Social Media Specialist Radio Oz Bandung dengan menggunakan dalam pengelolaan media sosial dengan menggunakan teori Kompetensi Komunikasi milik Brian Spitzberg dan Willian Cupach. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan studi deskriptif. Hasil penelitian ini menunjukkan bahwa untuk menjaga konsistensi, Social Media Specialist Radio Oz Bandung harus memiliki motivasi selalu mencari tren terkini yang diminati masyarakat di berbagai platform media sosial. Didukung oleh pengetahuan konten dan prosedural yang mereka miliki dalam mengoptimalkan media sosial, pengetahuan yang dimiliki social media specialist Radio Oz Bandung dalam mengatur konten sangat penting untuk memastikan bahwa konten tersebut menarik bagi audiens. Selain itu, Social Media Specialist Radio Oz Bandung mengembangkan strategi kontennya yang berfokus pada gaya hidup, musik, dan radio. Dengan itu Social Media Specialist Radio Oz Bandung dalam membangun komunikasi digital yang efektif, mereka mengandalkan keterampilan teknis serta keterampilan komunikasinya seperti copywriting, editing, dan desain untuk mengelola konten yang menarik perhatian audiens.